Elementary school science teachers' reflection for nature of science: Workshop of NOS explicit and reflective on force and motion learning activity - Khanittha Patho (2018)
© 2018 Author(s). The nature of science has been part of Thailand's science education curriculum since 2008. However, teachers lack of understanding about the nature of science (NOS) and its teaching, particularly element school science teachers. In 2012, the Science Institute of Thailand MOE, started a project of Elementary Science Teacher Professional Development to enhance their thinking about the Nature of Science. The project aimed to enhance teachers' understanding of NOS, science teaching for explicit and reflective NOS, with the aim of extending their understanding of NOS to other teachers. This project selected 366 educational persons. The group was made up of a teacher and a teacher supervisor from 183 educational areas in 74 provinces all Thailand. The project provided a one week workshop and a year's follow up. The week-long workshop consisted of 11 activities of science teaching for explicit reflection on 8 aspects of NOS. Workshop of NOS explicit and reflective on force and motion learning activity is one of eight activities. This activity provided participants to learn force and motion and NOS from the traditional toy "Bang-Poh". The activity tried to enhance participants to explicit NOS for 5 aspects including empirical basis, subjectivity, creativity, observation and inference, and sociocultural embeddedness. The explicit NOS worksheet provided questions to ask participants to reflect their existing ideas about NOS. The paper examines elementary school science teachers' understanding of NOS from the force and motion learning activity which provided explicit reflection on 5 NOS aspects. An interpretive paradigm was used to analyse the teachers' reflections in a NOS worksheet. The findings indicated that majority of them could reflect about the empirical basis of science and creativity but few reflected on observation and inference, or sociocultural embeddedness. The paper will explain the teachers' NOS thinking and discuss the further enhancing of their understanding and organizing NOS explicit and reflective science teaching.